THE ROLE OF TEAMWORK IN CREATING A STRATEGY FOR THE DEVELOPMENT OF AGRICULTURAL ENTERPRISES IN THE CONTEXT OF GLOBALIZATION CHANGES - SAKUN, Lesia; VIEDIENINA, Yuliia; KOSHYTSKYI, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This article explores the theoretical and practical aspects of the strategy for developing agricultural enterprises. It also determines the role of teamwork in the context of globalization, the destruction of traditional supply chains, and the socio-economic crisis caused by large-scale invasions. Developing a business activity strategy is an important tool for ensuring competitiveness in the market under conditions of uncertainty and competition. It is a complex of actions aimed at achieving goals, rational use of resources, and obtaining maximum profitability in the future. The state of the agricultural sector in Ukraine is considered, the main problems and ways of solving them in the context of globalization are characterized. The main problem for most enterprises in the industry is a lack of working capital and a collapse of international credit programs. Liquidity problems are caused by low sales volumes and an increase in logistics costs. Obtaining greater profits is possible by reorienting towards oil crops, spring barley, spring wheat, peas, oats, buckwheat, and reducing corn cultivation. As a result of analyzing the strategies of agro-industrial sector enterprises, it was determined that companies engaged in product processing have positive results. The article analyzes the practical experience of leading agro-industrial enterprises: Kernel, MHP, HarvEast, IMC, Astarta. This text discusses the strategies used by companies during war. It emphasizes the importance of teamwork in developing a strategy and highlights the effectiveness of long-term strategies during crises. As a result of the study, it was determined that the effectiveness of the work of an agricultural enterprise depends to a greater extent on a long-term strategy and a reserve of financial resources, and anti-crisis measures play a smaller role.